Los procesos contables y sus efectos en los costos de producción de la Compañía UNIMUEBLES S.A. - Baque Baquerizo, Adonis Javier (2024)
In the research work THE ACCOUNTING PROCESSES AND THEIR EFFECTS ON THE PRODUCTION COSTS OF THE COMPAÑÍA UNIMUEBLES S.A. It is analyzed how the application of a costing method related to business activity can improve the distribution of its costs within a specific period. It is mainly based on the modification of processes to account for transactions related to the cost of sales. The correct distribution of the cost of sales in a production process allows the company to precisely identify the values invested in each of the production stages, from the purchase of raw materials to the general costs for their distribution......